'A tool to help me through the darkness': suffering and healing among teacher-practitioners of Ashtanga yoga. Issue 3 (1st July 2021) - Shaw, Alison
Abstract: Yoga is widely regarded as beneficial for physical and emotional health, and as a safe ancillary intervention for managing a range of psychological conditions. Evidence of injury, harm, and abuse in yoga traditions is difficult to square with this emphasis on healing. Drawing mainly from on online memoirs by long-term practitioners of Ashtanga yoga, this paper examines the relationship between suffering and healing in yoga, showing how long-term abuse can be perpetuated and injury sustained in a system widely understood and labelled by its practitioners as therapeutic. The paper argues that elements of healing and harm are present in the rituals of practice, the concepts that support it, and the power structure of the Ashtanga system. The system's organizational dynamics together with a therapeutic discourse that links suffering to its transcendence enabled the same kinds of abuse and trauma that Ashtanga yoga is purported to heal. The analysis raises questions about the overarching narrative of yoga as safe and healthy, and about the connections between healing and harm within therapeutic traditions.